2007
DOI: 10.1007/s00213-007-0820-1
|View full text |Cite
|
Sign up to set email alerts
|

Repeated methamphetamine treatment impairs spatial working memory in rats: reversal by clozapine but not haloperidol

Abstract: These findings suggest that repeated METH treatment induces impairment of working memory, which is associated with a dysfunctional ERK1/2 pathway in the hippocampus. Furthermore, clozapine may be effective for the treatment of METH-induced cognitive dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 38 publications
4
38
0
Order By: Relevance
“…In a previous study, we have demonstrated that repeated METH treatment in mice impairs long-term recognition memory after withdrawal, which is associated with a dysfunctional dopamine D1 receptor-extracellular signal-regulated kinase 1/2 (ERK1/2) pathway in the prefrontal cortex (PFC; Kamei et al 2006;Nagai et al 2007b;Ito et al 2007) and that METH-induced cognitive impairment is reversed by an atypical antipsychotic clozapine, but not haloperidol . We have also demonstrated that repeated METH treatment in rats impairs working memory in a delayed spatial winshift task using a radial arm maze and that clozapine, but not haloperidol, is effective in improving the METHinduced working memory deficit (Nagai et al 2007a). …”
Section: Introductionmentioning
confidence: 82%
“…In a previous study, we have demonstrated that repeated METH treatment in mice impairs long-term recognition memory after withdrawal, which is associated with a dysfunctional dopamine D1 receptor-extracellular signal-regulated kinase 1/2 (ERK1/2) pathway in the prefrontal cortex (PFC; Kamei et al 2006;Nagai et al 2007b;Ito et al 2007) and that METH-induced cognitive impairment is reversed by an atypical antipsychotic clozapine, but not haloperidol . We have also demonstrated that repeated METH treatment in rats impairs working memory in a delayed spatial winshift task using a radial arm maze and that clozapine, but not haloperidol, is effective in improving the METHinduced working memory deficit (Nagai et al 2007a). …”
Section: Introductionmentioning
confidence: 82%
“…However, chronic, rather than acute, administration of moderate doses (p2 mg/kg daily) can impair cognitive performance, including measures of working memory (Lee et al, 2011;Nagai et al, 2007) and object recognition memory (Arai et al, 2009;Ito et al, 2007;Noda et al, 2010). In fact, administering mice 1 mg/kg of MA daily for 7 days produces reliable deficits in object recognition memory even when assessed at least 1 week after drug cessation (Kamei et al, 2006;Lu et al, 2010;Mizoguchi et al, 2011).…”
Section: Animals Exposed To Ma Will Show Cognitive Decline Particulamentioning
confidence: 99%
“…In animals, in addition to cognitive decline produced by chronic moderate (p2 mg/kg daily) or escalating doses of MA, concomitant alterations have been observed in D2-like dopamine receptor and dopamine transporter binding (DAT) (Groman et al, 2012), tissue levels of dopamine and serotonin (Lu et al, 2010), NMDA receptor binding (Lee et al, 2011), glutamate receptor (mGluR5) expression (Reichel et al, 2011), pyramidal neuron cell firing (Parsegian et al, 2011), and novelty-induced hyperphosphorylation of extracellular signal-related kinase 1/2 (Ito et al, 2007;Kamei et al, 2006;Nagai et al, 2007). In humans, cross-sectional studies likewise show differences in the brain structure and function between MA-dependent and healthy control participants (for reviews, see Berman et al (2008); Chang et al (2007); Salo and Fassbender (2012)).…”
Section: Ma Abuse Will Be Associated With Changes In the Human Brainmentioning
confidence: 99%
“…Whether D4 agonists/D3 antagonists would enhance human recognition memory, however, remains to be determined. Despite similarities between the D2 and D3 receptor, the D2 antagonist raclopride had no effect on SOR with delays of 1 or 24 h (Kamei et al 2006;Nagai et al 2007). While raclopride did appear to impair SOR with a 1-min delay, impaired performance was seen at doses that also reduced both sample and choice phase exploration (Woolley et al 2003), arguing against a specific effect on memory.…”
Section: Introductionmentioning
confidence: 95%